AKULTURASI BUDAYA DALAM DAKWAH MAULANA MALIK IBRAHIM - Siswayanti, Novita; Yunani, Ahmad (Jurnal Ilmiah Pendidikan dan Keislaman, 2021)
Maulana Malik Ibrahim is one of the walisanga from Kashan Persia. He is known as the grandsyaikh of the walisanga in the Nusantara. He has had an influence on Islamic civilization in Gresik. He succeeded in acculturating the traditions of Persian civilization with Javanese traditions. He interacts and preaches in a dialogical manner and is accommodative to the traditions and culture of the local community. He is not only good at preaching, but skilled and skilled in various fields of life; farming, medicine, shipping and education. The method used in this research is descriptive qualitative with a historical approach. Field observations, interviews and document studies were then analyzed descriptively of cultural acculturation in Maulana Malik Ibrahim's da'wah. The results of this study show cultural acculturation in Maulana Malik Ibrahim's da'wah both religiously and socially scientist. Socially, he taught trade, equality and tolerance among people; he founded a pesantren inspired by the mandala of a Hindu-Buddhist educational institution; he cares for and maintains traditions such as muludan, kupatan, suronan. While scientifically he is known as a healer who specializes in treating water, verses from the Koran and herbs; he introduced astrology for sailing, farming and determining the time of prayer / hilal